Zithromax Z-Pak and the Biaxin BBQ (B) - Hennessy, Julie (London : SAGE Publications Ltd, 2017)
The Biaxin case deals with competition in the mature market for antibiotics designed for use in the treatment of bacterial respiratory infections. The case tells the story of how Pfizer's Zithromax stole the share dominance of an established brand, Abbott's Biaxin. The case deals with the importance in pharma markets of consumer (patient) and channel (physician and insurance payer) insight as well as pharmacological efficacy data.
Originally published in Hennessy, J. (2008). Zithromax Z-Pak and the Biaxin BBQ (B). 5-108-003(B). Evanston, IL: Kellogg School of Management, Northwestern University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; Pfizer Inc; electronic books; Abbott; Competition; Pharmaceutical industry